Development of a building life cycle carbon emissions assessment program (BEGAS 2.0) for Korea׳s green building index certification system. (January 2016) - Roh, Seungjun; Tae, Sungho; Suk, Sung Joon; Ford, George; Shin, Sungwoo
Abstract: Carbon emission reduction policies demand tighter building Life Cycle Assessment (LCA) qualification standards. However, it is widely believed that it will be difficult to efficiently reduce the carbon emissions of buildings with only a fragmentary revision of the qualification standards. For this reason, the Korean government has developed the Green Building Index Certification System (GBI certification system), which is a certification framework based primarily upon the carbon emissions of a building. There is currently no assessment program tailored to the GBI certification system. The purpose of this study is to develop the Building Life Cycle Carbon Emissions Assessment Program (BEGAS 2.0) to support Korea׳s GBI certification system. With a theoretical consideration of the GBI certification system, the building LCA qualification standards of other international green building certification systems were analyzed. These analyses enabled development of BEGAS 2.0 that reflects the characteristics of the GBI certification system and the current state of Korea׳s construction industry. Consequently, an appropriate building life cycle carbon emissions assessment program was developed, which can support Korea׳s GBI certification system effectively.